Short‐term effect of elevated CO2 concentration (0.5%) on mitochondria in diploid and tetraploid black locust (Robinia pseudoacacia L.). Issue 13 (22nd May 2017) - Xu, Fuling; Jiang, Mingquan; Meng, Fanjuan
Abstract: Recent increases in atmospheric CO2 concentration have affected the growth and physiology of plants. In this study, plants were grown with 0.5% CO2 for 0, 3, and 6 days. The anatomy, fluorescence intensity of H2 O2, respiration rate, and antioxidant activities of the mitochondria were analyzed in diploid (2×) and tetraploid (4×) black locust ( Robinia pseudoacacia L.). Exposure to 0.5% CO2 resulted in clear structural alterations and stomatal closure in the mitochondria. Reduced membrane integrity and increased structural damage were observed in 2× plants at 6 days. However, after 0.5% CO2 treatment, little structural damage was observed in 4× plants. Under severe stress, H2 O2 and malondialdehyde were dramatically induced in both 2× and 4× plants. Proline remains unchanged at an elevated CO2 concentration in 4× plants. Moreover, the total respiration and alternative respiration rates decreased in both 2× and 4× plants. In contrast, the cytochrome pathway showed no decrease in 2× plants and even increased slightly in 4× plants. The antioxidant enzymes and nonenzymatic antioxidants, which are related to the ascorbate–glutathione pathway, were inhibited following CO2 exposure. These analyses indicated that 4× and 2× plants were damaged by 0.5% CO2 but the former were more resistant than the latter, and this may be due to increases in antioxidant enzymes and nonenzymatic antioxidants and stabilized membrane structure. Abstract : These analyses indicated that 4× and 2× plants were damaged by 0.5% CO2, but the former were more resistant than the latter, and this may be due to increases in antioxidant enzymes and nonenzymatic antioxidants and stabilized membrane structure.